1990
DOI: 10.1017/s0021932000018563
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of intercourse and contraceptive choice

Abstract: The effects of frequency of intercourse on perceptions of two of the most widely used contraceptive methods, the pill and condom, were assessed in 128 female college students currently involved in a sexual relationship. Intercourse frequency was found to be strongly associated with knowledge of both methods. People experiencing more frequent sexual intercourse were more favourably disposed towards the pill and less towards the condom than people experiencing intercourse less frequently. Implications of these r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
1

Year Published

1993
1993
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 11 publications
1
4
1
Order By: Relevance
“…U se of another form of contraception was a stronger correlate of condom use than relationship type. This study revealed th at respondents wh o had intercourse with a regular partner were m ore likely to report use of contraception other than condom sÐ a ® nding consistent with the sm all num ber of studies which have addressed this issue (Glor & Severy, 1990;Pilkington et al, 1994;Trñ en et al, 1992;W hitley, 1990). These results suggest that relationship status m ay be serving as a proxy m easure of use of other contraception.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…U se of another form of contraception was a stronger correlate of condom use than relationship type. This study revealed th at respondents wh o had intercourse with a regular partner were m ore likely to report use of contraception other than condom sÐ a ® nding consistent with the sm all num ber of studies which have addressed this issue (Glor & Severy, 1990;Pilkington et al, 1994;Trñ en et al, 1992;W hitley, 1990). These results suggest that relationship status m ay be serving as a proxy m easure of use of other contraception.…”
Section: Discussionsupporting
confidence: 82%
“…W hile these exp lanations focus on the sym bolic m eaning of condom use to regular sexual partners, an alternative explanation is that condom use m ay be less likely in regular relationships for m ore pragm atic reasons. Research suggests that as a regular relationship develops and intercourse occurs m ore frequently, sexual partners are likely to change from condom s to the O C P as their prim ary form of birth control (Glor & Severy, 1990;Pilkington et al, 1994;Trñ en et al, 1992;W hitley, 1990). Thus, relationship status m ay be serving as a proxy m easure of use of another form of contraception.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, as the effects of the AIDS epidemic become increasingly recognized and as individuals take advice from public education campaigns, increases in the use of condoms are likely to be observed (Agha 2001;Glor and Severy 1990). Establishing the link between condom use and childbearing is, however, a delicate matter, since those most receptive to warnings about the risks of HIV infection may also be those who have earlier accepted advice regarding the desirability of family planning and births limitation.…”
Section: Discussion: Pathways For the Association Between Hiv/aids Womentioning
confidence: 99%
“…However, as the sexual experience level increases among college students, the likelihood of contraceptive usage increases. Recent studies have indicated that about three fourths of college women report always using contraception, 71% (Pepe et al 1993) and 73% (Glor and Severy 1990), whereas only about one half (55%) of men report that contraception is always used (Adler and Hendrick 1991;Pepe et al 1993). Even if contraception is used, however, many college students fail to take precautions against contraction of a sexually transmitted disease by using a condom.…”
Section: Contraceptive Usagementioning
confidence: 99%
“…Even if contraception is used, however, many college students fail to take precautions against contraction of a sexually transmitted disease by using a condom. The percentage of college women who report condom usage during sexual intercourse all the time or almost always fluctuates from 16% (Glor and Severy 1990) to31%(L Carroll 1991).…”
Section: Contraceptive Usagementioning
confidence: 99%